University Legal Learning Spaces Effectiveness in Developing Employability Skills of Future Law Graduates - Jason James Turner; Puteri Sofia Amirnuddin; Harmahinder Singh Iqbal Singh (UUM Press, 2019)
Purpose â€" The objective of this study was to examine the role of legal learning space in a Malaysian university and how this space impacts on law studentsâ€™ preparation for the employment market. This study comes in response to the issue of inexperienced graduates, who lack appropriate employability skills for the world of work, commonly referred to as the â€˜graduate skills gapâ€™. Methodology â€" This study used an online survey (accessed via a QR code) on 256 law students at a university in Malaysia. The sample size comprised 213 currently enrolled students and 43 alumni, with the former cohort representing 95% of the total law student population at the university and the latter representing 17% of the total alumni population. Findings â€" The study found that students, regardless of their year of study, did not consider that legal learning space at the university replicated real life legal practice but thought that the space prepared them for employment. The students felt that some legal learning space was better than others in developing their employability skills. Despite this they enjoyed interacting in the space collectively and felt that it helped them improve their teamwork, communication and soft skills. It also revealed that the perceptions of legal learning space could be improved with better management of staff and student expectations. Significance â€" This study was one of few studies, which investigated the role of learning space in developing law studentsâ€™ employability skills set. The findings helped to consolidate existing research in the area of graduate skills gap, the development of graduate employability skills, and in advancing research on identifying studentsâ€™ perception of learning space and the specific skills students felt they had developed while engaged in this space. This study will be of particular interest to both employers and universities as they seek to manage each otherâ€™s expectations and pursue a more practice-based learning curriculum.